Challenges and potential solutions of grid-forming converters applied to wind power generation system—An overview - Huang, Liang; Wu, Chao; Zhou, Dao; Chen, Liang; Pagnani, Daniela; Blaabjerg, Frede (Frontiers in Energy Research, 2023)
As the capacity of wind power generation increases, grid-forming (GFM) wind turbine generators are deemed as promising solutions to support the system frequency for future low inertia power grids. So far, the GFM converter with a nearly ideal dc voltage source has been studied thoroughly. However, when the GFM converter is applied to wind power applications, there are some realistic problems and challenges, such as coordinating wind turbine control and GFM control, limited energy to support the grid, variable wind speed, etc. These problems still need more discussion. In this paper, an overview of challenges and potential solutions of GFM converters applied to wind power generation systems are provided, where different energy reserving schemes, GFM control schemes, and overcurrent protection schemes are compared and discussed. Finally, a few perspectives on future trends are shared according to the authors’ knowledge.